TINDAK PIDANA DAN PERTANGGUNGJAWABAN PIDANA PENGEMBANG PERUMAHAN DAN KAWASAN PERMUKIMAN DALAM PENYEDIAAN PRASARANA, SARANA DAN UTILITAS UMUM BERDASARKAN UNDANG-UNDANG NOMOR 1 TAHUN 2011 TENTANG PERUMAHAN DAN KAWASAN PERMUKIMAN - Nurpanca Sitorus; Alvi Syahrin; Suhaidi Suhaidi; Mahmud Mulyadi (USU LAW JOURNAL, 2014)
ABSTRACT As a housing developer who is responsible for carrying out the construction of the PSU is not free from criminal responsibility if negligent or intentionally does not perform its obligations. Criminal offenses committed by the Real Estate Developer in the provision of infrastructure, facilities, and public utilities in the development of housing and residential areas under Law No. 1 of 2011 on Housing and Settlement Zone, namely mengalihfungsikan infrastructure, facilities, and public utilities outside the function, sell units settlements, before finishing the status of land rights or Lisiba residential environment first, develop the housing, which does not build housing in accordance with the criteria, specifications, requirements, infrastructure, facilities, and public utilities agreed, build housing and / or settlements outside the region specifically earmarked for housing and settlements, build housing, and / or settlements in place that could potentially pose a danger to people or goods Keywords: Crime, Criminal Responsibility, Real Estate Developer and Settlement Regions.